PEMUSNAHAN BARANG SITAAN TINDAK PIDANA NARKOTIKA DALAM RANGKA PENCEGAHAN PENYIMPANGAN PEREDARAN KEMBALI BARANG SITAAN DI MASYARAKAT (STUDI PADA KEJAKSAAN NEGERI BELAWAN) - Aisyah Aisyah; Alpi Sahari (JURNAL DOKTRIN REVIEW, 2022)
Narcotics confiscated goods that have been decided by the Court and have a decision that has permanent legal force, there are still very many that are not immediately destroyed, of course this has the risk of irregularities where the prohibited goods can be circulated back to the community. In carrying out the action of destroying narcotics evidence according to Article 26 paragraph 1 PP No. 40 of 2013 concerning the Implementation of Law No. 35 of 2009 concerning narcotics, law enforcement agencies that are allowed to destroy narcotics evidence are BNN investigators and POLRI investigators, and prosecutors. And there are 5 (five) factors in the obstacles to the destruction of confiscated goods from narcotics crimes. First; the legal factor itself, Second; law enforcement factors, Third; factor of facilities or facilities, Fourth; community factor. The Belawan District Prosecutor's Office has taken preventive action, namely control is carried out to prevent the possibility of undesirable things from happening in the future, preventive or preventive actions are carried out by the Belawan District Prosecutor's Office as the executor of the Court Decision, aiming to protect against bad things that may occur, such as loss or misuse of confiscated narcotics. It is recommended that in carrying out the destruction of confiscated narcotics, a joint decision be drawn up between the Police, BNN, Prosecutor's Office, Court, regarding the evidence submitted to the Prosecutor's Office, only the remaining laboratory results do not need a maximum of 10 grams, this is done to prevent irregularities from circulating narcotics back into the community.